Effect of fresh blood transfusion in the treatment of sclerema neonatorum - Erwin Sarwono; F. X. Marseno; R. Kwari Satjadibrata; A. R. Polanunu (Indonesian Pediatric Society, 1973)
There is still confusion in the proper knowledge of Sclerema. At least 3 different conditions with induration of the subcutaneous fat in the neonatal period and in the first months of life exist which are called Sclerema (Djojodiguno, 1965; Nelson, 1959). In this paper, sclerema neonatonun is defined a.s a condition characterized by a diffuse rapidly spreading, non-edematous, tallow-like hardening of the subcutaneous tissue of infants in the first weeks of life. The skin of the involved areas cannot be picked up and the subcutaneous tissue seems fixed on to the subjacent muscles and bones (Hughes and Hammond, 1948).